Nacionalismo y política artístico-cultural de la dictadura chilena: la secretaría de relaciones culturales - Isabel Jara Hinojosa (Nuevo mundo - Mundos Nuevos, 2016)
This article describes the contribution of Department of Cultural Relations on the artistic and cultural discourse of the dictatorship, analyzing their coordination with the government's cultural apparatus, his path in the vagaries of government policy and the ideological conflicts that influenced on it. It suggests that the identification of the SRC with the nationalism allowed it to prolong the life and make narrative sense to the hesitant and weak “cultural policy”, through a anti-marxist, essentialist and heroic story; but, at the same time, it was trapped in the paradox of publicize it consistent with the internationalizing and modernizing trend of neoliberalism, and the aesthetics opening of the art circuit.